Relation between baseline LDL-cholesterol and cardiovascular outcomes in high cardiovascular risk hypertensive patients: A post-hoc SPRINT data analysis. (1st July 2019) - Nguyen, Lee S.; Procopi, Niki; Salem, Joe-Elie; Squara, Pierre; Funck-Brentano, Christian
Abstract: Background: Patients at increased cardiovascular (CV) risk, noticeably hypertensive patients, have multiple CV risk factors which may be treatment targets. LDL-cholesterol is one of such targets. Using the SPRINT cohort, studying the cardiovascular outcomes of hypertensive patients at increased CV risk, this post-hoc study aimed to assess the association of LDL-C with CV outcomes. Methods: Clinical outcomes were those defined in SPRINT: a composite of various CV outcomes, all-cause mortality, and CV mortality. Association between LDL-C and the primary outcome was analyzed using survival regression adjusted on confounding factors (age, sex, body-mass index, active smoking status, eGFR-estimated kidney function, history of CV disease, Framingham risk score, SPRINT treatment arm (intensive or control), baseline high-density-lipoprotein-bound cholesterol, and co-treatments by aspirin and statins). Results: LDL-C was not associated with the primary outcome in the overall cohort ( n  = 9631). Among patients in secondary prevention (i.e. with a previous history of CV disease) ( n  = 1562), LDL-C was marginally associated with the incidence of the primary outcome (adjusted hazard-ratio 1.005 (95% CI = 1.002–1.009), p  = 0.005 (per 1 mg/dl increase)) however, discrimination was poor with a ROC AUC of 0.54, p  = 0.087. There was no association between LDL-C and the primary outcome in other subgroup analyses (those under statin or not, and those in primary prevention). Conclusion: This post-hoc analysis of SPRINT indicates that LDL-C levels do not influence cardiovascular events over a period of 3 years in a large cohort of hypertensive patients at increased risk of cardiovascular events but without previous history of clinical cardiovascular disease other than stroke. Highlights: There was no association between baseline LDL-cholesterol and cardiovascular outcomes in the overall cohort and it was mild in patients in secondary prevention. There was no association between baseline LDL-cholesterol and cardiovascular outcomes in other subgroup analyses (statin use, primary prevention). No LDL-C threshold could serve as a reliable target to accurately predict cardiovascular events. This adds to the debate against using LDL-C levels as a treat-to-target approach in these patients.